Temporomandibular Joint Pathology of Wild Carnivores in the Western USA - Rickert, Siobhan S.; Kass, Philip H.; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2021)
Skull specimens from: southern sea otter (Enhydra lutris nereis), Eastern Pacific harbor seal (Phoca vitulina), California sea lion (Zalophus californianus), northern fur seal (Callorhinus ursinus), walrus (Odobenus rosmarus), polar bear (Ursus maritimus), North American brown bear (Ursus arctos), American black bear (Ursus americanus), California mountain lion (Puma concolor couguar), California bobcat (Lynx rufus californicus), gray fox (Urocyon cinereoargenteus), kit fox (Vulpes macrotis), and gray wolf (Canis lupus) (n = 5,011) were macroscopically examined for dental and temporomandibular joint (TMJ) pathology. The presence of temporomandibular joint osteoarthritis (TMJ-OA) varied across species: 4.1% of southern sea otter, 34.5% of harbor seal, 85.5% of California sea lion, 20% of northern fur seal, 60.5% of walrus, 9.2% of polar bear, 13.2% of North American brown bear, 50% of American black bear, 20.9% of California mountain lion, 0% of California bobcat and gray fox, 6.3% of kit fox, and 11.6% of gray wolf specimens had lesions consistent with TMJ-OA. TMJ-OA was significantly more prevalent in males than females in walrus, North American brown bear, polar bear, American black bear, and California mountain lion (p < 0.001, p = 0.005, p = 0.005, p = 0.002, and p = 0.004, respectively). No other species showed a sex predilection. Adult specimens were significantly more affected with TMJ-OA than young adults in the harbor seal, fur seal, walrus (all p < 0.001), and kit fox (p = 0.001). Gray wolf and American black bear young adults were significantly (p = 0.047 and p < 0.001) more affected by TMJ-OA than adults. Of the 13 species analyzed, only three species, namely the harbor seal, northern fur seal, and polar bear, had a significant increase in the prevalence of TMJ-OA if their teeth had attrition and abrasion (p < 0.001, p < 0.001, and p = 0.033, respectively). TMJ-OA can lead to morbidity and mortality in wild animals, but its etiology is not yet fully understood.